“Gestión de riesgos mayores en el gobierno autónomo descentralizado del cantón Tisaleo: Elaboración del Plan de Emergencia” - Carrillo Mejía, Franklin Eduardo (2017)
Management of major risks in the Tisaleo Municipal Decentralized Autonomous Government: Elaboration of the Emergency Plan ABSTRACT: The main objective of this research was to carry out the Management of Major Risks in the Autonomous Municipal Government of Tisaleo with which the main threats were identified, whether of natural or anthropic origin, to which the three buildings of the Municipal GAD are exposed Of Tisaleo, thus complying with current regulations and creating a culture of prevention in its authorities in order to ensure the welfare of the people who carry out their activities within the establishment, as well as their infrastructure and facilities. In order to comply with our main objective, the threats and vulnerabilities to which the Municipal GAD of Tisaleo were exposed were identified through the application of the MEIPEE Method (Method for the Elaboration and Implementation of Emergency Plans for Companies), which resulted in a risk Of earthquake, volcanic eruption and fires; A fire risk assessment was performed using the MESERI (Simplified Method of Fire Risk Assessment) method. With the compilation of the information, the emergency plan of the Municipal GAD of Tisaleo was implemented, applying the format of the Ambato Fire Department, establishing suitable procedures for the purpose of preserving the welfare of all those who remain in the facilities. The Emergency Plan of the Tisaleo Municipal Decentralized Autonomous Government was approved by the Tisaleo Fire Department and registered by the Zonal Risk Management Secretariat 3. Then the emergency plan was implemented with which a reaction time was obtained that was smaller than the estimated for the number of people who perform their daily activities in the Municipal GAD.